NF-I proteins from brain interact with the proenkephalin cAMP inducible enhancer. - Chu, H M (1991)
A short region of the human proenkephalin promoter has been shown previously to mediate transcriptional regulation in response to activation of the cAMP, TPA, and Ca+ + dependent intracellular signalling pathways. Two adjacent DNA elements, CRE-1 and CRE-2, are essential for this regulation although neither element alone is sufficient for inducible expression. The CRE-2 element consists of overlapping binding sites for the transcription factors AP-1 and AP-4. The CRE-1 element has been shown to interact with a DNA binding factor called ENKTF-1. Here we characterize proteins from bovine brain which bind the CRE-1 element of the human proenkephalin gene. Interactions between proteins binding the CRE-1 and CRE-2 elements are characterized in vitro using affinity purified DNA binding proteins. We demonstrate that CRE-1 binding proteins from bovine brain consist of three different polypeptides each belonging to the NF-I family of transcription factors. Point mutation analysis of the contacts of these proteins with the CRE-1 element indicate that NF-I proteins contact the inducible enhancer at the sequence CTGGCxxxxxxCCT which overlaps the CRE-1 element (underlined) defined by in vivo point mutation analysis. Cotransfection of one of the three NF-I proteins purified from bovine brain, NF-I/Red1, together with a proenkephalin/bacterial chloramphenicol acetyl transferase (CAT) fusion gene repressed protein kinase A or forskolin stimulated CAT expression.